GAMBARAN ALKOHOL DALAM URIN PEMINUM ALKOHOL DENGAN METODE KALIUM DIKROMAT - Situmorang, Ing Mayfa; Ladyka Viola A.A; Asbar Tanjung; Athifah Febry Alfiani (Rena Cipta Mandiri, 2025)
Alcohol detection methods have gone through significant development with various methods such as gas chromatography, strip test, and potassium dichromate. Potassium dichromate method is a simple method to detect alcohol in urine with the principle of oxidation reaction between alcohol and potassium dichromate in an acidic atmosphere between alcohols forming a green color. This study aims to identify alcohol in the urine of male alcohol drinkers aged 17-50 years using the potassium dichromate method. The research method used was descriptive experimental. The population in this study were all alcohol drinkers in Cakung Timur Village who met the exclusion and inclusion criteria. The sample used in this study was 30 samples. The sampling technique used was purposive sampling. The method used is potassium dichromate method. The results showed that the potassium dichromate method can detect blood alcohol content through urine obtained 29 respondents (98.7%) positive and 1 respondent (1.13%) negative.